Sorption Energies for Atrazine onto Devolatalized Vitellaria paradoxa - Adams Udoji Itodo; Funke Wosilat Abdulrahman,; Lawal Gusau Hassan; Ugbede Itodo Happiness (Iranian Journal of Chemistry & Chemical Engineering, 2012)
We utilize isotherm models in contributing to scholarly knowledge in simple terms, to measure the forces or energy defining certain adsorption phenomenon. Gas Chromatography coupled with Mass Spectrophotometer detector (GCMS) was utilized to measure equilibrium phase atrazine after adsorption onto Shea nut Shells (SS) acid derived activated carbon. Data were fitted into the D-R and Temkin isotherm relationships for energy data estimation of Sorption energy value (BD), mean free energy (ED) and heat of sorption (B). They were estimated as 0.7600mol2KJ-2, 0.8111 kjmol-1 and  0.790Jmol-1 respectively. The parameter predicting  the type of adsorption was evaluated BD , B < 20kJ/mol and ED2 = 0.979 proves a better choice in explaining sorption energies. Generally, shea nut shells can be used as alternative precursors for activated carbon production via the two steps and acid treatment method..